ANALISIS USAHA MENTAL (UM) MAHASISWA SEBAGAI GAMBARAN EXTRANOUS COGNITIVE LOAD (ECL) DALAM KEGIATAN PERKULIAHAN PENDIDIKAN BIOLOGI: (Analysis of Student’s Mental Effort as an Image of Extranous Cognitive Load in Biology Education Lecture Activities) - Iffa Ichwani Putri; Sepita Ferazona (UIR Press, 2019)
This study aims to determine the level of Extranous Cognitive Load (ECL) of students through mental effort in learning activities. Mental effort can be known and analyzed from external or foreign aspects, such as learning design and learning strategies undertaken. The source of the burden obtained in the learning process is known as ECL. The effectiveness of ECL is influenced by information and learning activities that contribute to the process of constructing students' cognitive schemes in learning process received. Good learning process happen if the ECL owned by student is in low category. ECL is measured by the mental effort of students in attending lecture activities. This research is a descriptive study, which was carried out on the fourth semester students of biology education who took part in the ethics and professional education classes. ECL measurements were measured using a mental effort questionnaire during the lecture. The data acquired is analyzed on the conversion of values in the low to high categories. The results showed that in the lecturing activities the student’s mental effort average was in the low category at 32.45. A low mental effort represents a low extranous cognitive load (ECL). It can be concluded that the learning strategies carried out in the ethics and education professional lectures can suppress ECL biology education students.